2018
DOI: 10.1029/2018gl077728
|View full text |Cite
|
Sign up to set email alerts
|

Observed NO/NO2 Ratios in the Upper Troposphere Imply Errors in NO‐NO2‐O3 Cycling Kinetics or an Unaccounted NOx Reservoir

Abstract: Observations from the SEAC 4 RS aircraft campaign over the southeast United States in August-September 2013 show NO/NO 2 concentration ratios in the upper troposphere that are approximately half of photochemical equilibrium values computed from Jet Propulsion Laboratory (JPL) kinetic data. One possible explanation is the presence of labile NO x reservoir species, presumably organic, decomposing thermally to NO 2 in the instrument. The NO 2 instrument corrects for this artifact from known labile HNO 4 and CH 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 66 publications
1
54
0
Order By: Relevance
“…LNO x (p) is the LNO x vertical profile calculated by the difference of vertical profiles between WRF-Chem simulations with and without lightning. Please note that the CP is a reflectance-weighted pressure retrieved by the collision-induced O 2 -O 2 absorption band near 477 nm (Acarreta et al, 2004;Sneep et al, 2008;Stammes et al, 2008). For a deep convective cloud with lightning, the CP lies below the geometrical cloud top, which is much closer to that detected by thermal infrared sensors, such as CloudSat and the Aqua Moderate Resolution Imaging Spectrometer (MODIS) (Vasilkov et al, 2008;Joiner et al, 2012).…”
Section: Methods For Deriving Amfmentioning
confidence: 93%
See 2 more Smart Citations
“…LNO x (p) is the LNO x vertical profile calculated by the difference of vertical profiles between WRF-Chem simulations with and without lightning. Please note that the CP is a reflectance-weighted pressure retrieved by the collision-induced O 2 -O 2 absorption band near 477 nm (Acarreta et al, 2004;Sneep et al, 2008;Stammes et al, 2008). For a deep convective cloud with lightning, the CP lies below the geometrical cloud top, which is much closer to that detected by thermal infrared sensors, such as CloudSat and the Aqua Moderate Resolution Imaging Spectrometer (MODIS) (Vasilkov et al, 2008;Joiner et al, 2012).…”
Section: Methods For Deriving Amfmentioning
confidence: 93%
“…Recent studies revealed that the modeled NO/NO 2 ratio departs from the data in the SEAC 4 RS aircraft campaign (Travis et al, 2016;Silvern et al, 2018). Silvern et al (2018) attributed this to the positive interference on the NO 2 measurements or errors in the cold-temperature NO−NO 2 −O 3 photochemical reaction rate.…”
Section: Effects Of Cloud and Lno X Parameterization Onmentioning
confidence: 99%
See 1 more Smart Citation
“…The partitioning of NO x into NO and NO 2 in GMI/GEOS‐Chem, which affects the AMF, has been re‐examined recently by Travis et al () and Silvern et al (). They found GEOS‐Chem NO/NO 2 ratios near and above 10 km to be approximately a factor of 2 larger than those of in situ measurements from the SEAC 4 RS campaign.…”
Section: Discussionmentioning
confidence: 99%
“…Autooxidation of organic compounds in low-NO environments is increasingly recognized as a key source of highly-oxidized/low-volatility organic compounds in the atmosphere (Crounse et al, 2013). Measurements of the ratio of NO to nitrogen dioxide (NO 2 ) in the upper troposphere (UT) frequently cannot be reconciled with models (Cohen et al, 2000;Silvern et al, 2018). Zhao et al (2019) show that differences in background NO at the single pptv level are responsible for differences in global modeled OH on the order of 50%.…”
Section: Introductionmentioning
confidence: 99%